Effect of zinc and copper on the growth characteristics, yield, essential oil composition, and antimicrobial properties of Thai basil (Ocimum basilicum var. thyrsiflora) cultivated in Vietnam - T. V. Giang; T. T. Huyen; L. T. T. Huyen; V. N. Lan (Труды по прикладной ботанике, генетике и селекции, 2025)
Thai basil (Ocimum basilicum var. thyrsiflora (L.) Benth.) (Lamiaceae) is widely used for its aromatic leaves and culinary value. This study investigated the effects of zinc (Zn; 0, 10, 20 mg/kg of soil) and copper (Cu; 0, 5, 10 mg/kg of soil), individually and combined, on the growth, yield, essential oil composition, and antimicrobial properties of Thai basil grown in Vietnam. The optimal plant responses, including increased height, lateral branches of the stem number, fresh and dry yield of green mass, and essential oil yield, were achieved at Zn 10 mg/kg and Cu 5 mg/kg. The major essential oil components were linalool (41.64-53.27%), and methyl chavicol (22.45-37.56%), with the highest concentrations recorded at Zn 10 mg/kg and Cu 5 mg/kg. Antimicrobial tests showed strong activity of essential oil against Staphylococcus aureus, Escherichia coli, and Candida albicans, with minimum inhibitory concentrations (MIC) between 25 and 100 qg/mL. However, higher levels of Zn and Cu negatively impacted growth, yield, and oil quality. The study highlights the importance of regulating Zn and Cu levels in soil to optimize the growth and essential oil properties of Thai basil. These findings offer valuable guidance for enhancing the agricultural production of Thai basil, balancing both quantity and quality.